Blue Ocean Strategy Desa Sumberagung Sebagai Desa Wisata Unggulan Banyuwangi - Ayu Wanda Febrian; Dora Melati Nurita Sandi; Firda Rachma Amalia (UNIVED Press, 2022)
Banyuwangi is currently focusing on the development of tourism development area II with its main attraction being Sukomade. Sumberagung Village is one of the villages in the area. Sumberagung Village has potential as a tourist village , but does not yet have a tourism village development model that can be used as management guidelines. This causes the absorption and use of village funds to be less fully absorbed so it is necessary to formulate a special strategy for tourism villages. This research is focused on making a strategy design with the Blue Ocean Strategy approach with a four-step framework analysis, namely Eliminate, reduce, raise and create. Through the approach of eight aspects of forming a tourist village, the results of the study show that Sumberagung Village is in the development stage so the focus of the development strategy that is considered appropriate is fitness tourism by maximizing the creation of new tourist attractions.